Application of open domain adaptive models in image annotation and classification. - Sheng Li; Zhousheng Chang; Haizhen Liu (PLoS ONE)
In the field of computer vision, the task of image annotation and classification has attracted much attention due to its wide demand in applications such as medical image analysis, intelligent surveillance, and image retrieval. However, existing methods have significant limitations in dealing with unknown target domain data, which are manifested in the problems of reduced classification accuracy and insufficient generalization ability. To this end, the study proposes an adaptive image annotation classification model for open-set domains based on dynamic threshold control and subdomain alignment strategy to address the impact of the difference between the source and target domain distributions on the classification performance. The model combines the channel attention mechanism to dynamically extract important features, optimizes the cross-domain feature alignment effect using dynamic weight adjustment and subdomain alignment strategy, and balances the classification performance of known and unknown categories by dynamic threshold control. The experiments are conducted on ImageNet and COCO datasets, and the results show that the proposed model has a classification accuracy of up to 93.5% in the unknown target domain and 89.6% in the known target domain, which is better than the best results of existing methods. Meanwhile, the model check accuracy and recall rate reach up to 89.6% and 90.7%, respectively, and the classification time is only 1.2 seconds, which significantly improves the classification accuracy and efficiency. It is shown that the method can effectively improve the robustness and generalization ability of the image annotation and classification task in open-set scenarios, and provides a new idea for solving the domain adaptation problem in real scenarios.